(untitled) (Triyuga Academic Journal, 2021)
Education is a human capital investment, which is expected to yield results that will translate to the improvement and growth of the economy of a nation. So this paper explores the importance of education in economic development, the relation between education and the economy, and the impact of education on the economy. The effect can be seen in areas with a high percentage of well-educated people who can channel their knowledge into concrete actions that lead to the development of the economy in comparison to those areas where there are few well-educated people. A country’s economy becomes more productive as the proportion of educated workers increases since educated workers can more efficiently carry out tasks that require literacy and critical thinking.